Energy Dissipation Reduction Using Similarly-Charged Polymer-Surfactant Complex - Abdulbari, Hayder A.; Faraj, Emsalem; Jolius, Gimbun; Mahmood, Wafaa K. (Pushpa Publishing House, 2015)
Transporting viscous liquids in pipelines is considered as one of the most energy consuming sectors in the industry due to the turbulent flow mode associated. High molecular weight polymers are effective drag reduction agents for enhancing liquid flow through pipelines, but they typically break apart (mechanical degradation) when subjected to high shear forces. Introducing a surfactant to the polymer to form a polymer-surfactant complex is a known technique to minimize the mechanical degradation. However, most available polymer-surfactant complexes formed of oppositely charged additives tend to exhibit low drag reduction performance. In the present study, we chose a different approach by investigating the drag reduction performance and mechanical degradation resistance of a similarly charged polymersurfactant complex using a rotating disk apparatus (RDA). Additionally, transmission electron microscopy (TEM) was used to gain an in-depth perspective into the polymer-surfactant complex structure. The experimental results showed that rigid complexes are successfully formed and exhibit improved drag reduction performance and mechanical degradation resistance. © 2015 Pushpa Publishing House, Allahabad, India.